2007
DOI: 10.1007/bf03194241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human disturbance on movement, foraging and bed selection in red deerCervus elaphus xanthopygus from the Wandashan Mountains, northeastern China

Abstract: Z. 2007. Effects of human disturbance on movement, foraging and bed selection in red deer Cervus elaphus xanthopygus from the Wandashan Mountains, northeastern China. Acta Theriologica 52: 435-446.We characterized 716 sites (including 22 beds, 60 foraging and 604 movement sites) used by red deer Cervus elaphus xanthopygus Milne-Edwards, 1867 in the Wandashan Mountains, northeastern China in the winter period. We used covariates for vegetation, topography, disturbances by other ungulates, and disturbance by hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…On the other hand, our results also suggested that moose may have some scope for behavioral plasticity under human influences in northeastern China, compared with behaviors of moose in other regions (Jepsen and Topping 2004). The behavior of moose is similar to avoidance by red deer (Cervus elaphus xanthopygus) of forest roads in northeastern China (Jiang et al 2007). Avoidance by red deer was detected up to 1.6 km from forest roads, up to 8.2 km from villages, and up to 2.2 km from abandoned roads (Jiang et al 2007).…”
Section: Human Disturbancesmentioning
confidence: 63%
“…On the other hand, our results also suggested that moose may have some scope for behavioral plasticity under human influences in northeastern China, compared with behaviors of moose in other regions (Jepsen and Topping 2004). The behavior of moose is similar to avoidance by red deer (Cervus elaphus xanthopygus) of forest roads in northeastern China (Jiang et al 2007). Avoidance by red deer was detected up to 1.6 km from forest roads, up to 8.2 km from villages, and up to 2.2 km from abandoned roads (Jiang et al 2007).…”
Section: Human Disturbancesmentioning
confidence: 63%
“…Forestry development is of considerable concern, but assessment of its impacts in China has been constrained to those directly related to forest harvest activities. Furthermore, researchers have only focused on responses of ungulates to human disturbances without considering quantification of habitat availability change (Jiang et al 2006(Jiang et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we could reveal the dynamics of probability of occurrence with the change in disturbance distance or time intervals. Similar approaches were used to assess the impacts of human actions on the availability of habitats for grizzly bears and red deer behavioural occurrence in northeastern China (Suring et al 1998, Jiang et al 2007.…”
Section: Creation and Evaluation Of Resource Selection Function Modelsmentioning
confidence: 99%
“…However, historically, the main predators of C. e. alxaicus, the snow leopard, Uncia uncia (Schreber,1775); the gray wolf, Canis lupus Linnaeus, 1758; and lynx, Lynx lynx (Linnaeus, 1758), became extinct during the 1980s in the Helan mountain region (WANG & SCHALLER 1996). Numerous studies have demonstrated that deer behavior and habitat use are mostly influenced by humans (BORKOWSKI & UKALSKA 2008), including hunting, other human activities (LICOPPE 2006), travel routes JIANG et al (2007) reported that C. e. xanthopygus in northeastern China showed some behavioral plasticity in response to human influences, and the effect of habitat loss or fragmentation caused by human activities are expected to be great (JAEGER et al 2005). However, in the Helan Mountain region, we found that the deer neither preferred nor avoided human disturbance (p > 0.05) (Appendix 1), and they profited from the programs of ForestGrass Conservation Project and Shelterbelt Forestry Project and Returning Husbandry to Forestry (Grass) launched in 1996 (ZHAO et al 2000(ZHAO et al 2004, respectively.…”
Section: Discussionmentioning
confidence: 99%